Modelling the cost-effectiveness and budget impact of pay-for-performance programs in health care - Afschin Gandjour (BMC, 2024)
Abstract Introduction With an upward trend in adoption by industrialized nations, pay-for-performance (P4P) mechanisms are increasingly recognized for fostering quality improvement in healthcare. P4P programs conventionally reward providers with supplemental payments upon achieving predefined performance targets. This study aims to utilize decision modelling to determine the cost-effectiveness and maximum incentive levels of P4P programs. Methods A decision model, grounded in previously published models exploring the cost-effectiveness of implementation programs, was developed. The model evaluates the cost-effectiveness of P4P programs for an exogenous reward size under varied reward mechanisms and also in scenarios with and without a budget or time constraint. Results In instances where P4P programs do not substitute other healthcare programs, their incremental cost-effectiveness ratio (ICER) is deterministically set and ranges from treatment ICER to infinity, irrespective of the reward mechanism. With a budget or time constraint in play, the P4P program is incentivized up to the point where its population cost or ICER aligns with that of the program being replaced. Conclusion The proposed decision model effectively calculates the cost-effectiveness and budget impact of P4P programs, accommodating various reward mechanisms and scenarios, both with and without budget or time constraints.